Adverse events associated with encorafenib plus binimetinib in the COLUMBUS study: incidence, course and management - Gogas, Helen J; Flaherty, Keith T; Dummer, Reinhard; Ascierto, Paolo A; Arance, Ana; Mandala, Mario; Liszkay, Gabriella; Garbe, Claus; Schadendorf, Dirk; Krajsova, Ivana; Gutzmer, Ralf; Sileni, Vanna Chiarion; et al. (European journal of cancer (Oxford, England, 2019)
BACKGROUND: Dual inhibition of the mitogen-activated protein kinase pathway with BRAF/MEK inhibitor (BRAFi/MEKi) therapy is a standard treatment for BRAFV600-mutant metastatic melanoma and has historically been associated with grade III pyrexia or photosensitivity depending on the combination used. The objective of this study was to fully describe adverse events from the COLUMBUS study evaluating the most recent BRAF/MEK inhibitor combination encorafenib+binimetinib. PATIENTS AND METHODS: Patients with locally advanced, unresectable or metastatic BRAFV600-mutant melanoma were randomised to receive encorafenib 450 mg once daily plus binimetinib 45 mg twice daily, encorafenib 300 mg once daily or vemurafenib 960 mg twice daily. Adverse events that represent known effects of available BRAFi and/or MEKi were evaluated. RESULTS: The safety population included a total of 570 patients (encorafenib+binimetinib = 192; encorafenib = 192; vemurafenib = 186). Median duration of exposure was longer with encorafenib+binimetinib (51 weeks) than with encorafenib (31 weeks) or vemurafenib (27 weeks). Common BRAFi/MEKi toxicities with encorafenib+binimetinib were generally manageable, reversible and infrequently associated with discontinuation. Pyrexia was less frequent with encorafenib+binimetinib (18%) and encorafenib (16%) than with vemurafenib (30%) and occurred later in the course of therapy with encorafenib+binimetinib (median time to first onset: 85 days versus 2.5 days and 19 days, respectively). The incidence of photosensitivity was lower with encorafenib+binimetinib (5%) and encorafenib (4%) than with vemurafenib (30%). The incidence of serous retinopathy was higher with encorafenib+binimetinib (20%) than with encorafenib (2%) or vemurafenib (2%), but no patients discontinued encorafenib+binimetinib because of this event. CONCLUSION: Encorafenib+binimetinib is generally well tolerated and has a low discontinuation rate in patients with BRAFV600-mutant melanoma, with a distinct safety profile as compared with other anti-BRAF/MEK targeted therapies. TRIAL REGISTRATION: ClinicalTrials.gov (Identifier: NCT01909453) and with EudraCT (number 2013-001176-38).
Keywords: Male; Safety; zvracení; lidé středního věku; Vomiting; protokoly protinádorové kombinované chemoterapie; protoonkogenní proteiny B-Raf; Carbamates; únava; Mitogen-Activated Protein Kinases; Mutation; sulfonamidy; vemurafenib; karbamáty; melanom; benzimidazoly; Humans; Skin Neoplasms; inhibitory proteinkinas; Melanoma; Benzimidazoles; Middle Aged; Nausea; Vemurafenib; mužské pohlaví; Antineoplastic Combined Chemotherapy Protocols; Female; Protein Kinase Inhibitors; mitogenem aktivované proteinkinasy; Sulfonamides; Encorafenib; Binimetinib; ženské pohlaví; nádory kůže; incidence; Incidence; nauzea; mutace; lidé; Proto-Oncogene Proteins B-raf; Fatigue